Desempenho agronômico de cultivares de amendoim no Paraná para rendimento de grãos, teor de óleo e qualidade fisiológica de sementes - Ribeiro, Gidiane Prado (2013)
The peanut (Arachis hypogaea L.) is an oilseed. The seed of peanut butter has about 50% oil content. This crop has great potential as a feedstock for the biodiesel program implemented by the Brazilian government. The aim of this study was to investigate the agronomic performance of 12 peanut cultivars in 18 environments in the Paraná State. Another objective was to study the conditions that may influence the physiological quality of seeds produced and stored by the farmers themselves, by multifactor test with five factors: cultivars (IAC 886 and IAC Runner Tatu ST), locations, (Irati, Londrina and Santa Tereza do Oeste), packaging (paper bag, plastic bag and PET bottle), environments (cold chamber and ambient temperature) and time stored period. It was concluded that there were significant effects for cultivars, environments (years, seasons and locations) and the genotype x environment interaction for shelled grain yield and oil content in peanut seeds. The cultivars IAC Tatuí, IAC Tupã and BRS Havana showed high yield. High oil content was verified in the cultivars BRS 151-L7, IAC Tatuí and BRS Havana. The adaptability analysis for grain yield showed the following results: the cultivars Runner IAC 886 and IAC Caiapó showed specific adaptation to unfavorable environments, while IAPAR 25 Tição and IAC Tupã favorable. The cultivar IAC Tatu ST was more stable for grain yield. The physiological quality of peanut seeds is influenced by cultivars, locations, environments and time stored period. Physiological statistically superior quality was observed in the cultivar IAC Tatu ST, seeds produced in Londrina, the environment cold chamber and the second period seeds storage. The packaging used (paper bag, plastic bag and PET bottle) didn t influence the seeds viability, however the PET bottles showed up handling more practical and agile.